Language education and digital technologies today: Opportunities or risks? - Miłkowska-Samul, Kamila (Kwartalnik Neofilologiczny, 2026)
This study critically examines the integration of digital technologies and generative artificial intelligence in foreign language teaching through a netnographic approach on Facebook groups and teachers’ social media profiles. Three critical issues were identified: the fragmentation of linguistic input mediated by social media platforms, quality problems in teaching materials produced by creators lacking pedagogical training or generated by AI, and the commodification of the language teaching process. These issues compromise the coherence of learning pathways and the systematicity of language acquisition. The study reaffirms the central role of teachers as critical mediators capable of consciously integrating technologies and developing in students the critical thinking necessary to navigate the digital ecosystem.